Coupling Robot-Aided Assessment and Surface Electromyography (sEMG) to Evaluate the Effect of Muscle Fatigue on Wrist Position Sense in the Flexion-Extension Plane - Mugnosso, Maddalena (Front Hum Neurosci, 2019)
Proprioception is a crucial sensory modality involved in the control and regulation of coordinated movements and in motor learning. However, the extent to which proprioceptive acuity is influenced by local muscle fatigue is obscured by methodological differences in proprioceptive and fatiguing protocols. In this study, we used high resolution kinematic measurements provided by a robotic device, as well as both frequency and time domain analysis of signals captured via surface electromyography (sEMG) to examine the effects of local muscle fatigue on wrist proprioceptive acuity in 16 physically and neurologically healthy young adults. To this end, participants performed a flexion/extension ipsilateral joint position matching test (JPM), after which a high-resistive robotic task was used to induce muscle fatigue of the flexor carpi radialis (FCR) muscle. The JPM test was then repeated in order to analyze potential changes in proprioceptive acuity. Results indicated that the fatigue protocol had a significant effect on movements performed in flexion direction, with participants exhibiting a tendency to undershoot the target before the fatigue protocol (−1.218°), but overshooting after the fatigue protocol (0.587°). In contrast, in the extension direction error bias values were similar before and after the fatigue protocol as expected (pre = −1.852°, post = −1.237°) and reflected a tendency to undershoot the target. Moreover, statistical analysis indicated that movement variability was not influenced by the fatigue protocol or movement direction. In sum, results of the present study demonstrate that an individual’s estimation of wrist joint displacement (i.e., error bias), but not precision (i.e., variability), is affected by muscular fatigue in a sample of neurologically and physically healthy adults.